Fundamental framework for strengthening human trafficking victims’ rights in Malaysia - Ab Hamid, Zuraini (2017)
Despite the achievements of 19th-century abolitionists, currently, human trafficking is the fastest growing criminal enterprise in the world. The Trafficking in Persons (TIP) reports from 2012 until 2016 states that Malaysia has issues in three (3) main areas in combatting human trafficking. They are related to the laws and policies, the enforcement and the prosecution in handling human trafficking. The reports further mentioned that the major criteria which contributed to Malaysia’s positioning in the low tiers in the TIP were due to its ineffective of laws and policy in protecting the trafficking victims. This criteria has resulted to Malaysia’s worst position at Tier 3 in the TIP 2014. The latest TIP report 2016 has disclosed that the government of Malaysia has been continuingly giving poor treatment to the victim. The existing policy has increased the risk of exploitation on the victim by the employer when they are incapable of paying the immigration fees. Refugees in Malaysia also have lack of formal status or the ability to obtain work permits under the Malaysian law, making them vulnerable to trafficking. Many have incurred large smuggling debts where the traffickers used as a subject of debt bondage to some refugees. It is clear that Part V of the ATIPSOM 2007 provides protection for trafficking victims, but its adequacy in protecting the victims is still in doubt. Instead of having extensive efforts, comprehensive laws and a group of enforcement bodies in Malaysia, the fight against human trafficking is a never ending battle. In this study it is found that there are many efforts should be taken by the government of Malaysia in order to improve its legal, policies and institutional frameworks that promote and protect the rights of human trafficking victims.